Paxillus involutus enhances drought resistance of Pinus sylvestris seedlings by improving photosynthetic rate and water use efficiency - Musella, Paola; Lalaymia, Ismahen; Verdonck, Rik; Colpaert, Jan; Ponette, Quentin; Declerck, Stéphane (Frontiers in Forests and Global Change, 2025)
IntroductionScots pine (Pinus sylvestris) is an important tree species that is often regenerated through seedling establishment. The resistance of these seedlings to drought treatments and their recovery are essential to forest regeneration. The association with ectomycorrhizal (EcM) fungi such as Paxillus involutus has the potential to improve drought resistance and possibly recovery. Here, we conducted two experiments to evaluate the impact of P. involutus inoculation on growth and water use of pine seedlings under contrasting drought intensities.MethodsIn the first experiment, EcM fungal-inoculated and non-inoculated seedlings were subjected to well-watered (100% field capacity—control treatment) or low-watered (10% field capacity for 1 week—drought treatment) conditions, followed by a recovery phase in a semi-hydroponic cultivation system. In the second experiment, seedlings were initially subjected to well-watered or moderate water conditions (100 and 30% field capacity, respectively), followed by prolonged low-watered conditions (10% field capacity for 1 month), each followed by a recovery phase.ResultsIn the first experiment, EcM fungal-colonized pine seedlings showed increased aboveground biomass, higher photosynthetic rates, water-use efficiency, and elevated nitrogen and phosphorus contents under low-water conditions. In the second experiment, a prolonged low-water regime reduced root colonization by the EcM fungus. During recovery, P. involutus-inoculated seedlings had an increase in ammonium assimilation under well-watered conditions and appeared to recover more efficiently, in particular from prolonged low-water conditions, with higher chlorophyll production, possibly due to increased nutrient availability and/or fungal demand.DiscussionOur results suggest that the benefits of P. involutus depend on both water regime and drought duration: a short-term low-water regime (10% field capacity for 1 week) enhances EcM benefits, while under a moderate water regime (30% field capacity) the fungal effect was not evident. We conclude that P. involutus can confer significant benefits to pine seedlings, making it a valuable strategy for forest regeneration in temperate climates facing drought episodes.